Neo-Tectonism and Quantitative Morphotectonic Analysis of Roste Valley at Imbricated-Suture Zones, Kurdistan Region, Iraq - Paiwast Zhazhlayi; Ali Surdashy (Iraqi Geological Journal, 2022)
The morphotectonic analysis was done of the Roste valley, within the Imbricated and Suture zone of the Zagros Fold,Thrust Belt. The formations of the Imbricate Zone are of Jurassic and Cretaceous ages and the Suture Zone is covered by Zagros nappes of the Tertiary period. The Zagros Fold-Thrust Belt passes through several stages and tectonic phases. During the last stage of the Zagros Fold-Thrust Belt development from the Savian to Valahian and Pasadenian tectonic phases, the study area is influenced by active tectonic activity which is reflected by geomorphic properties in each subbasin. The migration of the Roste stream across oblique fault leaves 7 levels of the river terraces which are also signs of Neotectonics. The study area is divided into 18 subbasins for the morphotectonic analysis through applying geomorphic indices (HI, SL, Vf, Af, Smf, and Bs) and accordingly the index of relative active tectonics was indicted. The morphotectonic study reveals that the index of relative active tectonics is higher in the Suture Zone than in the Imbricated Zone. The index of relative active tectonics of the Suture Zone’s subbasins ranges from high to very high neotectonics activity (1.67-1.17), whereas of the Imbricate Zone’s subbasins ranges from medium to high active tectonic activity (2.33-1.67). The results are related to morphotectonic indices that show the balance between the tectonic and erosion process.